2021
DOI: 10.1016/j.jtumed.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Rising prevalence of multidrug-resistant uropathogenic bacteria from urinary tract infections in pregnant women

Abstract: Objectives This study aimed to determine the prevalence of urinary tract infections (UTI) in pregnant women and characterise the uropathogenic bacterial strains associated with symptomatic and asymptomatic bacteriuria in Lahore, Pakistan. Methods Between December 2018 and June 2019, we analysed the uropathogenic bacterial strains from midstream urine samples in 80 pregnant women. The age of the pregnant women ranged from 19 to 45 years, and they resided in urban and rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
4
18
0
1
Order By: Relevance
“…Regarding to our study, MDR in Gaza governmental hospitals is (37%) for E. coli and (53%) for Klebsiella spp., respectively. We demonstrated very high prevalence of Gramnegative isolates and this in agreement with a study in Lahore, Pakistan conducted between December 2018 and June 2019, which reported that prevalence of 92%Gram negative [13]. Another study in Ethiopia reveled that Gram-negative bacteria caused 90% of UTI cases while gram-positive bacteria cause only 10% of the cases [14].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding to our study, MDR in Gaza governmental hospitals is (37%) for E. coli and (53%) for Klebsiella spp., respectively. We demonstrated very high prevalence of Gramnegative isolates and this in agreement with a study in Lahore, Pakistan conducted between December 2018 and June 2019, which reported that prevalence of 92%Gram negative [13]. Another study in Ethiopia reveled that Gram-negative bacteria caused 90% of UTI cases while gram-positive bacteria cause only 10% of the cases [14].…”
Section: Discussionsupporting
confidence: 91%
“…This is in concomitant to the findings in Pakistan in which the highest MDR was observed in Klebsiella species and other microorganisms. 33 Also similar finding to our present study was highlighted by Nteziyaremye et al, in Eastern Uganda where some isolates were found to have a high level of multidrug resistance especially for Pseudomonas species, Klebsiella species and Staphylococcus aureus. 39…”
Section: Microorganisms (N) Discussionsupporting
confidence: 92%
“…Other findings have been reported in Turkey, Ethiopia, Cameroon, NigeriaPakistan, and India where Escherichia coli and Klebsiella pneumoniae were the first and second most prevalent pathogens. 2,7,28,[34][35]23,9,25,26,33,31,38 Some authors reported Staphylococcus species or Streptococcus pyogenes to be the second most common uropathogen; but accounting for the third cause of bacteriuria in our study. Variation in geographical location, uses of antibiotic with or with-out prescription by qualify medical personnel are common in rural and urban settlements which may have accounted for these differences.…”
Section: Microorganisms (N) Discussionsupporting
confidence: 47%
See 2 more Smart Citations